Tradução, adaptação transcultural e avaliação psicométrica do Pediatric Asthma Control and Communication Instrument - PACCI - Santino, Thayla Amorim (2018)
Introduction: In Brazil, a prevalence of about 20 million individuals with asthma is observed mainly in childhood and adolescence, and the occurrence of its symptoms is closely related to the lack of control of the disease. Objectives: To perform a translation, cross-cultural adaptation, and evaluation of psychometric properties of the Pediatric Asthma Control and Communication Instrument (PACCI) for use in the Brazilian population. Methods: The translation and cross-cultural adaptation involved the translation, backtranslation, multiprofessional committee of experts and pre-test in a representative sample of the new population. The psychometric properties were evaluated through the administration of the adapted version of the questionnaire in a sample of 103 children and adolescents with clinical diagnosis of asthma and their parents/caregivers. The socioeconomic condition was evaluated (Brazil Economic Classification Criteria); clinical control (Childhood Asthma Control Test (c-ACT) and Asthma Control Test (ACT)); caregiver’s quality of life(Pediatric Asthma Caregivers Quality of Life Questionnaire (PACQLQ)), and pulmonary function (spirometry). We investigated the validity (content, construct and concurrent), reliability and the cutoff. Results: The multiprofessional committee of experts indicated that the items of the questionnaire were clear and compressible, with agreement ranging from 0.78 to 1.00. In the pre-test, parents/caregivers presented a good understanding of the items (agreement above 0.90). The internal consistency was 0.80. The internal structure of the questionnaire was evaluated through exploratory factorial analysis (KMO=0.81 and Bartlett’s sphericicity test, p<0,001), considering the extraction of 4 pre-determined factors and orthogonal rotation (varimax).The following factors were identified: clinical control, risks, perception of asthma status and severity. The factor asthma control showed a significant correlation with c-ACT/ACT, PACQLQ. For the control factor, the problem index and the sum of the score indicated that a score of 1 and 4 points were indicative of uncontrolled asthma, respectively. Conclusion: The Brazilian version of the questionnaire PACCI showed to be able to provide valid and reliable measures to assess the clinical control of asthma in children and adolescents.